Which Governments May Control the Mass Media: Iran and Kurdistan as a Case Study? - Ahmad, Araz Ramazan (Journal of Economic Development, Environment and People, 2015)
Abstract This paper is the comparative study in order to discover the motives of using censorship on Media. The main argument of this study is to determine the "Using of Censorship on Media in different government states” Consistently, the study depends on document analysis method and academic sources as well. Correspondingly, the study focuses on Media and democracy and then Mass Media in Iran and Kurdistan region of Iraq. Finally, the law of press in Iran and Kurdistan will be analysis to know the key elements of censorship in both governments.